Quantification of abscisic Acid, cytokinin, and auxin content in salt-stressed plant tissues - Dobrev, Petre I; Vankova, Radomira (Methods in molecular biology (Clifton, N.J.), 2012)
Plant hormones cytokinins, auxin (indole-3-acetic acid), and abscisic acid are central to regulation of plant growth and defence to abiotic stresses such as salinity. Quantification of the hormone levels and determination of their ratios can reveal different plant strategies to cope with the stress, e.g., suppression of growth or mobilization of plant metabolism. This chapter describes a procedure enabling such quantification. Due to the high variability of these hormones in plant tissues, it is advantageous to determine their content in the same sample. Reverse phase and ion exchange chromatography allows separation of the individual hormone fractions. Hormones as well as their metabolites can be identified and quantified by LC/MS.
Keywords: listy rostlin; Plants; Abscisic Acid; rostlinné extrakty; vysokoúčinná kapalinová chromatografie; Salt Tolerance; Plant Roots; kyseliny indoloctové; Mass Spectrometry; Salinity; Cytokinins; Chromatography, High Pressure Liquid; rostliny; kořeny rostlin; Stress, Physiological; salinita; cytokininy; tolerance k soli; Plant Extracts; Indoleacetic Acids; Plant Leaves; hmotnostní spektrometrie; fyziologický stres; kyselina abscisová